use matrices to solve the system of equations , if possible.

2x+y+2z=4
2x+2y=5
2x-y+6z=2

http://www.gregthatcher.com/Mathematics/GaussJordan.aspx

2 1 2 4

2 2 0 5
2-1 6 2

1 0 2 3/2
0 1-2 1
0 0 0 0

(3/2, 1, 0)

To solve the system of equations using matrices, we can represent the system in the form of an augmented matrix. Let's start by writing down the equation system:

2x + y + 2z = 4 -----> 2x + y + 2z = 4
2x + 2y = 5 -------> 2x + 2y = 5
2x - y + 6z = 2 -----> 2x - y + 6z = 2

Now, let's write the augmented matrix by putting the coefficients of the variables (x, y, z) and the constants on the right-hand side in a matrix form:

[ 2 1 2 | 4 ]
[ 2 2 0 | 5 ]
[ 2 -1 6 | 2 ]

The above matrix representation can be denoted as [A | B], where A represents the matrix of the coefficients of the variables and B represents the column matrix of the constants on the right-hand side.

To solve the system using matrices, we will perform row operations on the matrix [A | B] to transform it into an upper triangular matrix.

The goal is to use row operations to transform the matrix into the following form:
[ a b c | d ]
[ 0 e f | g ]
[ 0 0 h | i ]

Once we reach this form, we can easily solve for the variables starting from the bottom row.

Now, let's perform the row operations step by step:

1. Row 2 = Row 2 - Row 1
2. Row 3 = Row 3 - Row 1

The new matrix will be:
[ 2 1 2 | 4 ]
[ 0 1 -2 | 1 ]
[ 0 -2 4 | -2 ]

3. Row 3 = Row 3 + 2 * Row 2

The updated matrix will be:
[ 2 1 2 | 4 ]
[ 0 1 -2 | 1 ]
[ 0 0 0 | 0 ]

Now, the matrix is in upper triangular form. We can easily solve for the variables starting from the bottom row:

From the bottom row, we can see that 0z = 0, which means z can take any value (it is a free variable).

From the second row, we have 1y - 2z = 1. We substitute the value of z with a parameter (let's say t) to get y:

y - 2t = 1 -----> y = 2t + 1

Finally, from the first row, we have 2x + y + 2z = 4. Substituting the values of y and z obtained above:

2x + (2t + 1) + 2t = 4
2x + 4t + 1 = 4
2x + 4t = 3
x + 2t = 3/2
x = 3/2 - 2t

So, the solution to the system of equations is:
x = 3/2 - 2t
y = 2t + 1
z = t

Note that since z is a free variable, the system has infinitely many solutions.